HYPOGLYCEMIC AND ANTIOXIDANT POTENTIAL OF 1-DEOXYNOJIRIMYCIN IN HIGH GLUCOSE-INDUCED EXPERIMENTAL DIABETIC TILAPIA (Oreochromis niloticus) - LATHARAJA, R.; BANU, G. SHARMILA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The objective of the study was to assess 1-deoxynojirimycin's effects on high glucose levels and the tilapia Oreochromis niloticus (O. niloticus) propensities for hypoglycemia and antioxidant activity. O. niloticus' hypoglycemia was induced by adding glucose to the water of the fish pond. Glucose-given fishes were given either glibenclamide or the DJN. It was observed that DJN dissolves at doses of 10, 20 mg/kg b.w or glibenclamide (0.6 mg/kg b.w) tested in the fish's water. In comparison to the control group, the hypoglycemic-induced tilapia had greater blood sugar levels. After the induction of hypoglycemia, the blood glucose levels in tilapia were greater than in the control group for 90 minutes. The serum glucose level of the hypoglycemic tilapia was reduced by DJN or glibenclamide in a dose-dependent manner until it was comparable to that of the control group. According to the findings, DJN possessed anti-hypoglycemic action. This is the first study that we are aware of on the use of fish as a model for diabetes to test DJN or glibenclamide.